Treatment of Autoimmune Myasthenia Gravis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2004)
A treatment protocol for autoimmune myasthenia gravis (MG), patients sero-positive for AChR antibodies, is proposed from the University of California, Davis, CA.